2012
DOI: 10.1002/ange.201207730
|View full text |Cite
|
Sign up to set email alerts
|

5(4H)‐Oxazolones as Intermediates in the Carbodiimide‐ and Cyanamide‐Promoted Peptide Activations in Aqueous Solution

Abstract: We are indebted to the interdisciplinary program of the CNRS Planetary Environments and Origins of Life (EPOV) for support, and to the COST Action CM0703 "Systems chemistry" for providing the possibility of fruitful scientific exchanges during the realization of this work.Supporting information for this article is available on the WWW under http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…This finding suggested that the reactive amino acid species is H 3 N + ‐C(RR′)‐COO − (where R and R′ represent the amino acid side chains). It has also been proposed that cyanamide can activate N ‐acyl‐α‐amino acids to form a 5(4 H )‐oxazolone intermediate that can help facilitate the coupling of sterically hindered α‐amino acids 19. In addition, cyanamide has been suggested to be influential in other important prebiotic reactions, such as the synthesis of activated pyrimidine ribonucleotides20 and 2′‐deoxynucleotides 21…”
Section: Amino Acids Dipeptides and Dkps That Were Both Identified mentioning
confidence: 99%
“…This finding suggested that the reactive amino acid species is H 3 N + ‐C(RR′)‐COO − (where R and R′ represent the amino acid side chains). It has also been proposed that cyanamide can activate N ‐acyl‐α‐amino acids to form a 5(4 H )‐oxazolone intermediate that can help facilitate the coupling of sterically hindered α‐amino acids 19. In addition, cyanamide has been suggested to be influential in other important prebiotic reactions, such as the synthesis of activated pyrimidine ribonucleotides20 and 2′‐deoxynucleotides 21…”
Section: Amino Acids Dipeptides and Dkps That Were Both Identified mentioning
confidence: 99%
“…The stereochemical results obtained with both enantiomers of Ac-Ala can be explained by the intermediacy of 5(4H)-oxazolone 8a (Fig. 2), which is known to undergo racemization via an aromatic tautomer 8a' [32][33][34] and was further confirmed by an H/D exchange experiment (Fig. S24).…”
mentioning
confidence: 75%
“…[16] Preliminary experiments supported this scenario, [17] although the reaction seemed to be most favorable at acidic pH values lower than the pK 1 value of the amino acid. [19] In addition, cyanamide has been suggested to be influential in other important prebiotic reactions, such as the synthesis of activated pyrimidine ribonucleotides [20] and 2'deoxynucleotides. It has also been proposed that cyanamide can activate N-acyl-a-amino acids to form a 5(4H)-oxazolone intermediate that can help facilitate the coupling of sterically hindered a-amino acids.…”
mentioning
confidence: 99%
“…It has also been proposed that cyanamide can activate N-acyl-a-amino acids to form a 5(4H)-oxazolone intermediate that can help facilitate the coupling of sterically hindered a-amino acids. [19] In addition, cyanamide has been suggested to be influential in other important prebiotic reactions, such as the synthesis of activated pyrimidine ribonucleotides [20] and 2'deoxynucleotides. [21] Miller never carried out a detailed analysis of his 1958 cyanamide experiment, but he did measure the absorption at 280 nm when he collected various fractions during chromatographic separation of the discharge solution from the cyanamide experiment and found absorption in several samples where peptides were expected to elute.…”
mentioning
confidence: 99%